JFK and de Gaulle : How America and France Failed in Vietnam, 1961-1963 - McLaughlin, Sean J., 1978- (Book collections on Project MUSE., 2019)
"At the end of January 1963, France's ambassador to the United States, Herve Alphand, reported back to Paris on a top-secret American exercise at Camp David that revealed many of the stark differences between the two NATO allies. As Alphand, the Kennedy administration had decided the previous October to include representatives from Britain, France, and West Germany in a three-day series of politico-military simulations of potential conflict scenarios in divided Berlin. A French team took part in a series of strategic, limited conflict, and politico-military simulations from November 23 to 25, 1962, and while Alphand was impressed by the sheer planning and intellectual energy that went into this undertaking, he saw its glaring shortcomings. An exercise that Americans saw as a rational approach to the exigencies of the Cold War, the French found utterly dehumanizing. Intuition was discouraged, hindering creativity, yet the Americans believed that they could employ these methods to foresee every possible outcome during a given crisis--including the Vietnam War. In JFK and de Gaulle, Sean J. McLaughlin delves into the study of interstate Franco-American relations during the Kennedy presidency. He explains how John F. Kennedy came to view France as a world power from his college days at Harvard through to the end of his pre-presidential political career, while also exploring how and why France and the United States disagreed over the proper western strategy for the Vietnam War. McLaughlin also explores how de Gaulle's government made vigilant attempts to convince Kennedy that US military intervention in South Vietnam would backfire horribly; however, Kennedy chose not to heed de Gaulle's advice because he did not take France seriously as a member of the Atlantic alliance"--